Recontextualizing Tafsīr Lughawī: Bridging Linguistic Depth and Contemporary Qur’anic Interpretation - Ishfi Mufhimatul Uliyah; Abd. Kholid (KURAS Institute, 2025)
This study examines Tafsīr lughawī as one of the styles of Qur’anic interpretation that emphasizes a linguistic approach. This interpretive style emerged from an awareness of the importance of understanding the Qur’an through Arabic linguistic tools encompassing grammar, semantics, and rhetoric. The main purpose of this study is to comprehensively describe the definition, historical development, various types, characteristics, as well as the advantages and disadvantages of Tafsīr lughawī, along with the authenticity and significance of Tafsīr works that adopt the linguistic approach. This research employs a qualitative method using a library research approach, based on various classical and contemporary Tafsīr literatures. The findings show that Tafsīr lughawī significantly contributes to exploring the meanings of Qur’anic verses in depth through linguistic analysis. However, this approach also has limitations, particularly in the contextualization of social, historical, and maqāṣidī dimensions. Therefore, integration between Tafsīr lughawī and other approaches is essential to achieve a more complete and relevant understanding of the Qur’an in accordance with contemporary dynamics.